2010
DOI: 10.4081/hr.2010.e8
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Dysfunction in Hodgkin and Non-Hodgkin Lymphoma. A Paraneoplastic Syndrome?

Abstract: We wanted to determine whether autonomic dysfunction in patients with lymphoma is related to chemotherapy or represent a paraneoplastic syndrome. 40 patients with current or cured Hodgkin or non-Hodgkin lymphoma and 40 healthy controls, matched for age, gender, hypertension and diabetes mellitus underwent autonomic evaluation (Deep Breath, Valsalva Maneuver, Hand Grip, Lying to Standing, Tilt Test). Current patients also suffering from diabetes or hypertension, or still on chemotherapy revealed autonomic chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Both subclinical and clinical autonomic neuropathy were reported in association with Hodgkin lymphoma [15,16,17]. Autonomic neuropathy is a known risk factor for hypothermia in diabetic patients [18], mostly through excess vasodilatation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both subclinical and clinical autonomic neuropathy were reported in association with Hodgkin lymphoma [15,16,17]. Autonomic neuropathy is a known risk factor for hypothermia in diabetic patients [18], mostly through excess vasodilatation.…”
Section: Discussionmentioning
confidence: 99%
“…Orthostatic hypotension was not evaluated due to the patient's condition. Autonomic neuropathy in patients with Hodgkin lymphoma is probably a paraneoplastic phenomenon [15]. This could be aggravated by chemotherapy such as vinblastine or bleomycin, known to cause peripheral autonomic neuropathy [19], explaining the development of hypothermia after chemotherapy administration.…”
Section: Discussionmentioning
confidence: 99%
“…In the present report, the episodes of hypothermia developed prior to the administration of chemotherapy, demonstrating that, in our patient, other mechanisms must be involved in the development of the hypothermic episodes. Interestingly, in an observation study by Bilora et al it was concluded that a paraneoplastic phenomenon was the most likely explanation of the autonomic dysfunction observed in Hodgkin lymphoma [ 13 ]. At the time of the episodes of hypothermia, no diagnosis of malignant disease had yet been made.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of inhibition of counter-regulatory effects of these hormones on cytokine regulation could result in macrophage activation and NO production resulting in hypotension. 24 Salicylates have also been postulated to have a role in hypothalamic hypersensitivity. 12 Our patient never took any salicylates for his fever which rules this out as a possible cause.…”
Section: Discussionmentioning
confidence: 99%